Fixing the identity of Scolelepis squamata (Annelida: Spionidae) – neotype designation, redescription and DNA barcode sequences. Issue 1 (31st December 2022) - Surugiu, Victor; Schwentner, Martin; Meißner, Karin
Abstract : The identity of Scolelepis squamata (O.F. Müller, 1806 ) (Spionidae) has long been under debate. For clarification of this problem a collection of Scolelepis specimens at the type locality of this species, the island of Helgoland (North Sea) and in particular the Helgoland Dunes, has been undertaken. Based on morphological and molecular studies the occurrence of only one Scolelepis species can be reported in the eulittoral zone. The specimens are in good accordance with the morphology of S. squamata . Based on these newly collected specimens S. squamata is redescribed and illustrated comprehensively, and, in addition, molecular information on several markers is provided. A neotype has been designated and deposited in the collection of the Zoological Museum at Hamburg University, Germany. Molecular phylogenetic analyses based on COI, 18S rRNA and 28S rRNA reveal little genetic diversity along the Atlantic coast from Helgoland to Portugal and thus support the occurrence of S. squamata in these coastal regions of the Eastern North Atlantic Ocean. Our results further indicate the presence of a distinct Scolelepis species in the Black Sea, which is closely related to S. squamata . Also, S. mesnili is reinstated as a valid species. Furthermore, it is shown that several earlier genetic studies had misidentified S. squamata specimens wrongly as S. foliosa or S. bonnieri, highlighting the need for the taxonomic redescription as well as for providing DNA barcodes from unambiguously identified specimens. http://zoobank.org/urn:lsid:zoobank.org:pub:0D6C3783-FF06-4D84-8D92-B8691E88F0B9